2012
DOI: 10.1111/j.1095-8649.2012.03308.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and lunar cues are predictive of the timing of river entry and spawning‐site arrival in lake sturgeon Acipenser fulvescens

Abstract: The associations were quantified between daily and interannual variation in the timing of a closed population of lake sturgeon Acipenser fulvescens migration and arrival at spawning sites with stream environmental and lunar covariates. Spawning data were gathered from 1262 fish in Black Lake, Michigan 2001 to 2008 and by video monitoring 2000 to 2002. Sex‐specific variation in responses to external cues was also tested. Results showed that a greater number of individuals initiated migration from lake to riveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 73 publications
3
103
0
Order By: Relevance
“…In a similar study examining site fidelity, Forsythe et al (2012) found that individual spawning behavior was highly repeatable with respect to date and breeding site regardless of gender, size, or age, and it was less dependent, though still significantly linked, to water temperature, river discharge, and lunar phase. Repeatability in spawning time and location suggest that subpopulation differentiation may develop within populations, even within small and spatially contiguous areas.…”
Section: Spawning: Migrations and Habitat Selectionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a similar study examining site fidelity, Forsythe et al (2012) found that individual spawning behavior was highly repeatable with respect to date and breeding site regardless of gender, size, or age, and it was less dependent, though still significantly linked, to water temperature, river discharge, and lunar phase. Repeatability in spawning time and location suggest that subpopulation differentiation may develop within populations, even within small and spatially contiguous areas.…”
Section: Spawning: Migrations and Habitat Selectionmentioning
confidence: 90%
“…The above paragraphs demonstrate the diversity in depth (e.g., Chiotti et al 2008 versus Manny andKennedy 2002), velocity (Manny and Kennedy 2002), temperature (LaHaye et al 1992), and substrate type (LaHaye et al 1992). This coupled with the potential for subpopulations that may rely on differing cues (Forsythe et al 2012) creates a complex picture for a manager that must locate and protect sturgeon habitat based solely on the literature. This is an excellent example of how lake sturgeon knowledge from one area may not be applicable or useful in another.…”
Section: Spawning: Migrations and Habitat Selectionmentioning
confidence: 99%
“…use information on river discharge as well as current velocity and acceleration to make decisions about path choice [13, 4446]. While comparable studies with sturgeon have not been conducted, the reported relationship between river discharge and the timing of Lake Sturgeon spawning runs in the Black River system (Michigan, USA) [47] suggests that Lake Sturgeon are capable of detecting variation in hydraulic variables. Many fish species also use olfaction to home to natal habitats in rivers [48], but the use of chemosensory cues for route selection in the lower Detroit and St. Clair Rivers seems unlikely given that over 95% of the water flowing through Detroit-St. Clair river system emanates from a single source (Lake Huron).…”
Section: Discussionmentioning
confidence: 99%
“…Difficulty with the determination of sex in the field limited our ability to detect whether being male or female affected behavior after tag implantation, and thus, may have introduced some bias into our analyses. The seriousness of this potential bias is difficult to assess given that sex-based differences in lake sturgeon activity, movements, and migration timing have been observed in some systems [28,29] but not in others [30,31]. Reproductive status also should be considered as an explanatory variable in future tagging effects studies on lake sturgeon given that activity may be greatest during the post-spawn phase [29,30,32].…”
Section: Discussionmentioning
confidence: 99%